In the Shade of the Shady Tree: Stories of Wheatbelt Australia - Kinsella, John (Swallow Press, 2012)
In the Shade of the Shady Tree is a collection of stories set in the Western Australian wheatbelt, a vast grain-growing area that ranges across the southwestern end of the immense Australian interior. Kinsella’s stories offer glimpses into the lives of the people who call this area home, as the reader journeys from just north of the town of Geraldton to the far eastern and southern shires of the region.